Harnessing river geo-morphology and tidal wave to emulate reactor processes for bio-remediation of river - 214811 Mustafa Kamal Abdul Aziz; Sabariah Mohd. Yunus; Syaiful Nizam Hassan (Skudai : Universiti Teknologi Malaysia)
10